Analysys of Exam Questions Instrument Based on High Order Thinking Concept in Elementary Schools - Indriasari, Bernadine Ajeng (IJBLE Scientific Publications Community Inc., 2023)
Elemetary schools partner in Indonesia called Sekolah Dasar Mitra here in after referred as SDM are elementary schools which is having partnership with Primary Teacher Education study programs of Chatolic Musi Charitas University. The SDM should be choosen carefully. We should makesure they are implementing Kurikulum 2013 as well, included in the learning assessment process. The aim of this is to makesure the outcome of this study programme according to needed of employment in this era. This research using qualitative method. The analysis carried out on the structure of question of exam of SDM with High Order Thinking Skills (HOTS) criteria. The sample taking by random sampling method. The result showed 40 questions included on HOTS criteria dan 11 questions not included on HOTS criteria. HOTS question is about 78% dan other about 22%.